2019
DOI: 10.1038/s41467-019-13353-5
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-mediated regulation of a c-di-GMP phosphodiesterase in Vibrio cholerae

Abstract: Biofilm formation protects bacteria from stresses including antibiotics and host immune responses. Carbon sources can modulate biofilm formation and host colonization in Vibrio cholerae, but the underlying mechanisms remain unclear. Here, we show that EIIAGlc, a component of the phosphoenolpyruvate (PEP):carbohydrate phosphotransferase system (PTS), regulates the intracellular concentration of the cyclic dinucleotide c-di-GMP, and thus biofilm formation. The availability of preferred sugars such as glucose aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…Thus, the phosphorylation states of the PTS components are modulated in response to the available carbon source (Deutscher et al ., 2014). PTS components are also important as they play physiological roles by interacting with their cognate partners in a phosphorylation‐dependent manner (Deutscher et al ., 2006; Park et al ., 2013; Kim et al ., 2015; Park et al ., 2016; Choe et al ., 2017; Heo et al ., 2019). Furthermore, in Gram‐positive bacteria, it is known that the ATP‐dependent phosphorylation of HPr on the Ser‐46 residue by HPr kinase/phosphorylase (HPrK/P) (Mijakovic et al ., 2002) is involved in physiological regulation, such as carbon catabolite repression, by binding to the global transcription regulator, catabolite control protein A (CcpA) (Singh et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the phosphorylation states of the PTS components are modulated in response to the available carbon source (Deutscher et al ., 2014). PTS components are also important as they play physiological roles by interacting with their cognate partners in a phosphorylation‐dependent manner (Deutscher et al ., 2006; Park et al ., 2013; Kim et al ., 2015; Park et al ., 2016; Choe et al ., 2017; Heo et al ., 2019). Furthermore, in Gram‐positive bacteria, it is known that the ATP‐dependent phosphorylation of HPr on the Ser‐46 residue by HPr kinase/phosphorylase (HPrK/P) (Mijakovic et al ., 2002) is involved in physiological regulation, such as carbon catabolite repression, by binding to the global transcription regulator, catabolite control protein A (CcpA) (Singh et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Each of the carbohydrate genes specific to E. lacertideformus encoded various subunits of sugar phosphotransferase system (PTS) transporters. Sugar phosphotransferase system transporters are involved in signal transduction and in the transport and metabolism of sugars, all essential for modulating biofilm formation and EPS synthesis ( Loo et al, 2003 ; Lazazzera, 2010 ; Kawada-Matsuo et al, 2016 ; Heo et al, 2019 ). An additional E. lacertideformus -specific COG; glycerol-3-phosphate cytidylyltransferase (COG0615) may further correlate with the biofilm-forming capacity of this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…PTS components play multiple regulatory roles in enteric bacteria 53 . In V. cholerae , EIIA of glucose PTS influences biofilm formation via modulating the activity of cyclic di-GMP phosphodiesterase PdeS and regulating the decay of CsrB/C sRNA 54 , 55 . In this study, we showed that in response to the low O 2 signal in animal small intestine, V. cholerae turns off fruT and uptakes fructose via PTS, leading to the decrease of intracellular cAMP level and the enhanced expression of virulence genes.…”
Section: Discussionmentioning
confidence: 99%